Geometric design of solar-aided latent heat store depending on various parameters and phase change materials - Esen, M; Durmus, A; Durmus, A (Pergamon-Elsevier Science Ltd, 1998)
The cylindrical latent heat storage tanks considered here are part of a domestic heating system. In this study, the performances of such energy storage tanks are optimized theoretically. Two different models describing the diurnal transient behaviour of the phase change unit were used. The first is suited to tanks where the phase change material (PCM) is packed in cylinders and the heat transfer fluid (HTF) flows parallel to it (mode 1). The second is suited to tanks where pipes containing the fluid are embedded in the PCM (mode 2). The problem (treated as two-dimensional) is tackled with an enthalpy-based method coupled to the convective heat transfer from the HTF. A series of numerical tests are then undertaken to assess the effects of various PCMs, cylinder radii, pipe radii, total PCM volume in the tank, mass flow rates of fluid, and inlet temperatures of the HTF on the storing time. In addition, optimal geometric design of the store depending on these parameters and PCMs is presented. (C) 1997 Elsevier Science Ltd.
Keywords: Thermal-Energy Storage; System; Model; Simulation